Payment methods and patient satisfaction among type-2 diabetes patient at a teaching hospital in Malaysia - Essam AA,; Aniza Ismail,; Mohd Rizal AM,; Leny Suzana S,; Norlaila M,; Norlela Sukor,; Ahmed Abdelmajed A,; Syed Mohamed, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Diabetes mellitus is a costly chronic disease related to medication, physician consultation and laboratory investigation. The main means of financing healthcare include direct out-of-pocket (OOP) payment and government subsidisation in some countries, or public/private health insurance schemes, or a mix of all. Patient satisfaction is critical in ensuring the use of healthcare services, continuity of care and treatment adherence. In this study, we determined the satisfaction of type 2 diabetes mellitus (T2DM) patients regarding the healthcare services and payment methods at Universiti Kebangsaan Malaysia (UKM) Teaching Hospital, Malaysia. This cross-sectional study involved 313 T2DM patients aged ≥18 years who were included after clinical consultations. We used convenience sampling at the outpatient and inpatient medical centres of Hospital Canselor Tuanku Muhriz and UKM Specialist Centre. A survey consisting of sociodemographic, socioeconomic and payment method types as well as a validated patient satisfaction questionnaire scale were used. The mean age was 59.6 years (SD=13.151), 53.0% of the patients were female, 78.3% were Malay, 76.4% were uninsured, 39.6% were covered by government subsidies, while 36.7% paid OOP. Around 86% were generally satisfied with the overall services. Patients were most satisfied with technical quality (84%), communication skills (83%) and accessibility (80%), but satisfaction was lower in doctors’ service orientation, particularly the interpersonal manner (73%), financial aspect (73%) and time spent with the doctor (70%). Over 86% of patients were satisfied with healthcare services and payment methods; however, patients who paid OOP reported low satisfaction. Full insurance and extending benefits to partially cover both inpatients and outpatients with low co-payment is recommended to increase satisfaction.